THE ROLE OF MUSIC IN PATRIOTIC EDUCATION OF STUDENTS IN HIGH SCHOOLS - Kasimjonova Marjona Alisher kizi (Scholars Digest Publishing, 2023)
This article provides detailed information about the use of pedagogical technologies by music culture teachers in music culture classes in general education schools, the importance of music in educating students as patriots, well-rounded people, and instilling national values.
Keywords: culture, spirituality, music, national, patriotism, human, education, talent, experience.